2006
DOI: 10.1088/0953-8984/18/41/009
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structures of finite carbon nanotubes under external fields

Abstract: The electronic states of finite carbon nanotubes in the presence of electric and magnetic fields are calculated by the tight-binding model. Electronic properties such as state energy, energy gap, and density of states are mainly determined by the transverse electric field, the magnetic field, the Zeeman splitting, and the nanotube length, as well as the transverse geometric structure. The electric field could induce the destruction of state degeneracy, produce more low-energy states, and lead to significant ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The quantum-size effect has been verified by experimental measurements of transport properties [3][4][5][6][7][8]. For theoretical studies on 0D CNs, first-principles calculations and the tight-binding model are used to investigate electronic structures [9][10][11][12][13][14][15], magnetic properties [12][13][14][15], and optical excitations [13].…”
Section: Introductionmentioning
confidence: 88%
“…The quantum-size effect has been verified by experimental measurements of transport properties [3][4][5][6][7][8]. For theoretical studies on 0D CNs, first-principles calculations and the tight-binding model are used to investigate electronic structures [9][10][11][12][13][14][15], magnetic properties [12][13][14][15], and optical excitations [13].…”
Section: Introductionmentioning
confidence: 88%
“…The numerical results revealed that the band structure of carbon nanotubes is significantly changed under uniaxial stress when compared to BN nanotubes. Moreover, the reduction of band gap due to uniaxial stress is mainly considered to justify inducing the semiconductor–metal transition for CNTs while these changes do not take place for BN nanotubes. …”
Section: Introductionmentioning
confidence: 99%
“…Most recently, the effect of an external electric field on nanostructures has been of great interest in promising applications including nanoelectromechanical systems and other nanoscale devices because of the variation in the electronic and mechanical properties of the nanostructures. The electric field has a great impact on the electronic properties such as band gap tuning; semiconducting metallic transition; formation of an electric field dipole moment along the direction of applied field; and circular cross section to elliptical cross section deformation of C, BN, , SiC, and AlN nanotubes. However, the influence of the external electric field on the elastic properties of the nanotubes has not been studied extensively.…”
Section: Introductionmentioning
confidence: 99%